Historical Gardens in Cinema: Location, Transformation, Image / Исторический сад в кинематографе: натура, трансформация, образ - SOKOLOV BORIS M. / СОКОЛОВ Б.М. (Наука телевидения, 2022)
The article explores the roles of historical gardens in Western cinema. A garden can make a historical location (Versailles), mimic another historical garden (Vaux-le-Vicomte as Chantilly in Vatel), embody a national way of life (gardens of the National Trust in the 1995 TV series Pride and Prejudice), or be an abstract, to a greater or lesser extent, setting. In Atonement, the historical garden becomes a symbol, and in films about space (Silent Running) and the inner world metaphysics (The Fountain), the garden is reduced to a cultural archetype—a patch of turf, a spring, an old tree. One of the ways of utilizing the garden theme is its ironic presentation: the historical garden is shown as a ridiculous formal extravagance (The Draughtsman’s Contract) or as a costly project destroying the natural environment and the very life of the customer (The Serpent’s Kiss). The most intricate work with the theme of historical gardens was performed by Alain Resnais in Last Year at Marienbad. The nature for it was filmed in two Munich parks, and the formal interiors of Schleissheim Palace, with its countless mirrors, and the Rococo floral decor of the Amalienburg pavilion are continued in the views of the formal garden, which the director called “carved in stone.” A sculptural group, which the characters encounter in different parts of the park, represents their emotional states and existence on the border between reality and sleep. The conclusion is drawn that means. Among them are different levels of mediating documentary reality, utilization of cultural archetypes, and using the garden as a symbolic space. Статья посвящена роли исторических садов в зарубежном художественном кинематографе и вариантам их использования. Сад может быть исторической натурой (Версаль), играть роль другого исторического сада (Во-ле-Виконт в роли Шантийи в фильме «Ватель»), представлять национальный образ жизни (сады Национального Попечительского совета Англии в сериале «Гордость и предубеждение»), а также абстрагироваться в большей либо меньшей степени. Исторический сад, становящийся символом, использован в фильме «Искупление», а в фильмах о космосе («Молчаливое бегство») и метафизике внутреннего мира («Источник») сад сокращается до культурного архетипа — участок дерна, источник, старое дерево. Одним из вариантов освоения садовой темы становится ее ироническая подача: исторический сад показан как нелепая формальная затея («Контракт рисовальщика») либо как дорогостоящий замысел, разрушающий естественную природу и саму жизнь заказчика («Поцелуй змеи»). Наиболее сложная работа с темой исторического сада проведена в фильме Алена Рене «В прошлом году в Мариенбаде». Здесь натура снята в двух мюнхенских парковых резиденциях, причем формальный характер дворца с бесчисленными зеркалами и павильона Амалиенбург, украшенного флоральным декором рококо, продолжается в видах регулярного сада, который режиссер называет «выточенным из камня». Скульптурная группа, встречающаяся героям в разных частях парка, олицетворяет их эмоциональные состояния и существование на грани реальности и сна. В заключение сделан вывод о том, что тема исторического сада в кинематографе дает ему ряд уникальных художественных средств. Среди них — разные уровни опосредования документальной реальности, работа с культурными архетипами, использование сада в качестве символического пространства.